-5(7x-9)=-35x+45

Simple and best practice solution for -5(7x-9)=-35x+45 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(7x-9)=-35x+45 equation:


Simplifying
-5(7x + -9) = -35x + 45

Reorder the terms:
-5(-9 + 7x) = -35x + 45
(-9 * -5 + 7x * -5) = -35x + 45
(45 + -35x) = -35x + 45

Reorder the terms:
45 + -35x = 45 + -35x

Add '-45' to each side of the equation.
45 + -45 + -35x = 45 + -45 + -35x

Combine like terms: 45 + -45 = 0
0 + -35x = 45 + -45 + -35x
-35x = 45 + -45 + -35x

Combine like terms: 45 + -45 = 0
-35x = 0 + -35x
-35x = -35x

Add '35x' to each side of the equation.
-35x + 35x = -35x + 35x

Combine like terms: -35x + 35x = 0
0 = -35x + 35x

Combine like terms: -35x + 35x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| -8x-2=-x+3 | | 368=-7x+8(-5x-1) | | 5i^10= | | 15cos^2+(4cos)-3=0 | | 2y+4=-2x+6 | | 4x^2-60x-70=0 | | 6y=18x+36 | | (2+3i)(5-3i)(-7+I)= | | 6+4=-5 | | 6x-4=-50 | | (4+6i)-(5+3i)= | | 4x+4=29 | | x*7+46=221 | | 1.4(0.1)-0.1y=-7.9 | | 1.4(1.4)-0.1y=-7.9 | | -0.3x+9.79=-0.1x+3.39 | | 5x-10=38 | | x-40=-45 | | -2x-(5+4x)+4= | | 300x-0.36=800x+0.74 | | (-2x)-5+4x+4= | | 4(x-7.6)=1.6 | | 4x^2-20x=8 | | x-8=2.82 | | 3x^3-6x^2-x+5=0 | | 4x^4+6x^2+x+5=0 | | -2x-5+4x+4= | | 5s=2s+15 | | 3x^3+6x^2+x=-5 | | 24x+31x=21 | | 14p-10=8+p | | 8x^4+4x^3+2x^2+x=0 |

Equations solver categories